Dampak Pengelolaan Keuangan yang Efisien terhadap Keberlanjutan Usaha Tani Cengkeh: Studi Kasus di Kel. Induha Sulawesi Tenggara - Inar Andriani; Wa Ode Rayyani (CV. ITTC INDONESIA, 2025)
This study aims to analyze the impact of efficient financial management on the sustainability of clove farming in Induha Village, Southeast Sulawesi. The method used in this study is a qualitative approach with data collection through in-depth interviews and direct observation in the field. The results of the study indicate that good financial management, which includes budget planning, transaction recording, and financial report analysis, contributes significantly to increasing the productivity and profitability of clove farming. In addition, farmers who implement efficient financial management practices tend to be better able to face market risks and uncertainties, thereby increasing the sustainability of their businesses. This study recommends the need for training and assistance for farmers in financial management to support the sustainability of clove farming in the area.